(untitled) (Publicacions de la Universitat de València, 2024)
This book examines the ideological affinity that can be established between the classical ‘Bildungsroman’ and colonialist ideology on the basis of a literary analysis of Wilhelm Meisters Lehrjahre—considered by most critics to be the origin of the genre—and ‘Great Expectations’—one of the paradigmatic examples of the development of the Bildungsroman in English literature. This ideological affinity is understood as an example of what the Palestinian critic Edward Said has called the ‘structure of attitude and reference’: the convergence of different cultural manifestations that, although formally independent, contribute to a common purpose. The monograph also undertakes a study of the main characteristics of the classical ‘Bildungsroman’ from a formal and thematic point of view, and an analysis of the relationship between genre theories and Eurocentric discourses. Este libro examina la afinidad ideológica que puede establecerse entre el Bildungsroman clásico y la ideología colonialista a partir de un análisis literario del Wilhelm Meisters Lehrjahre (considerado por la mayoría de la crítica especializada como el origen del género) y de Great Expectations (uno de los ejemplos paradigmáticos del desarrollo de este género en las letras inglesas). Esta afinidad ideológica se entiende como una muestra de lo que el crítico palestino Edward Said ha llamado “structure of attitude and reference”: la convergencia de distintas manifestaciones culturales que, aunque son formalmente independientes, coadyuvan a un propósito común. Se estudian, también, las características principales del Bildungsroman clásico desde el punto de vista formal y temático, y se analiza la relación entre las teorías del género y los discursos eurocentristas.